O Supremo Tribunal Federal entre o direito e a política: as decisões sobre a presunção de inocência sob a perspectiva das teorias positivas estado-unidenses - Nathalia Brito de Carvalho (2022)
The discussion about the beginning of serving the sentence acquired the contours of a political-legal dispute in the period between 2016-2019, which may have been decisive for the constant changes in the position of the Federal Supreme Court on the subject. In the political context of Operation Lava-Jato (2014-2018), the controversies about corruption, incarceration and state punishment, added to the media spotlight directed at the court, ignited the controversies that involved the attribution of new meanings to art. 5th, LXII CR/88. With regard to the theme of judicialization of politics and in order to understand how politics was able to affect the interpretations of the court in the scope of constitutional law, the thesis has as its object habeas corpus 126.292/SP, habeas corpus 152.752/PR and Declaratory Actions of Constitutionality 43, 44 and 54 in the light of US positive theories. First, we will discuss the content of the Supreme Court ministers' decisions in a dogmatic perspective, addressing the historical and hermeneutical aspects of the principle, in addition to the criticisms of the STF ministers to the functioning of the Brazilian appeal system and its main dogmatic counterpoints. From there, the work follows an unconventional path: we argue, based on US positive theories, the problem of normative theories not being able to operate restrictions on judges. The second chapter will present the positive theories of Law as a possibility of renewing the dogmatic debate: we will (re)conceptualize, based on Robert Post, the relationship between Law and Politics as irrevocable, paradoxical and dynamic and we will approach the difference between the concepts of “influence” and “restriction” of the law on judges. With Barry Friedman, David Strauss, Laurence Tribe and Jack Balkin we bring some notes on the process of constitutional change. In Chapter 3 we will deal with the political-legal context regarding the judgment of actions on the limits of the presumption of innocence. Based on political science writings, we discuss how Operation Lava Jato (2014-2018) represents a shock to the Brazilian democratic construction. Then, based on Barry Friedman, we will present the “layers of politics” that exist in the court and that involved the decision on the principle of the presumption of innocence: the personal values of the judges and the appointment processes of ministers; the court's relationship with public opinion; relations within the collegiate of the Supreme; the “political game” that takes place between the Judiciary, Legislative and Executive Powers; the interaction of the court with the lower courts.